PENGARUH KUALITAS PRODUK, PROMOSI, DAN NILAI YANG DITERIMA TERHADAP KEPUASAN PELANGGAN MCDONALDS DI SHOPEE FOOD - Maulana, Rizki Akbar; Agus Abdurrahman (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
This research aims to identify factors from product quality, promotion, and value received to McDonalds customer satisfaction at Shopee Food. The type of data used is primary data. Primary data is data obtained from a research subject using measuring instruments or data collection tools as a direct source of information about the subject. The data for this study were obtained by distributing questionnaires to 150 respondents aged 16 to 35 years and analyzed using the Statistical Package for the Social Sciences (SPSS). The results of this research analysis show that there is a positive and significant influence between product quality on customer satisfaction, there is a positive and significant influence between promotion on customer satisfaction. There is a positive and significant influence between the value received on customer satisfaction and there is also a simultaneous influence between product quality, promotion, and value received on customer satisfaction. Based on the factors that influence customer satisfaction, the researchers studied are still broad and numerous. For this reason, researchers suggest looking for other variables that can affect customer satisfaction.